Determination of Women’s Gynecological Cancer Awareness Levels and Affecting Factors - Dulkara, Gamze Hilalcan; Abic, Arzu; Mamuk, Rojjin (AVES, 2024)
Objective: This descriptive study, aims to determine the level of women’s awareness on gynecological cancer in Turkish Republic of Northern Cyprus and the factors affecting their awareness. Methods: A total of 378 women participated in the study through an online questionnaire. Descriptive information forms and Gynecological Cancer Awareness Scale were used for data collection. The Statistical Package for Social Sciences version 25.0 software (IBM Corp.; Armonk, NY, USA) was used for data analysis. Mann–Whitney U-test was used to compare two groups, whereas the Kruskal–Wallis test was used to compare multiple groups. Results: The average Gynecological Cancer Awareness Scale score of the women included in the study was found to be 152.15 ± 18.31. Scale scores were found to be higher in women who used family planning methods, had knowledge about gynecological cancers, received information from healthcare professionals, had a gynecological examination once or more a year, had a Pap smear test,and performed self-vulva examinations. Conclusion: In this study, it was found that the awareness of gynecological cancer of women living in the Turkish Republic of Northern Cyprus was at a moderate level, and that the awareness of gynecological cancer was higher among women who had a higher level of education, had a good economic situation, underwent Pap smears, went to a gynecological examination once a year or more, and performed a self-vulva examination. © 2024 AVES. All rights reserved.
Keywords: awareness; Gynecological cancers; nursing; women’s health